Genomic evolution of BA.5.2 and BF.7.14 derived lineages causing SARS-CoV-2 outbreak at the end of 2022 in China - Wentao Zhu; Xiaoxia Wang; Xiaoxia Wang; Yujin Lin; Lvfen He; Rui Zhang; Chuan Wang; Xiong Zhu; Tian Tang; Li Gu (Frontiers Media S.A., 2023)
Since the end of 2022, when China adjusted its COVID-19 response measures, the SARS-CoV-2 epidemic has rapidly grown in the country. It is very necessary to monitor the evolutionary dynamic of epidemic variants. However, detailed reports presenting viral genome characteristics in China during this period are limited. In this study, we examined the epidemiological, genomic, and evolutionary characteristics of the SARS-CoV-2 genomes from China. We analyzed nearly 20,000 genomes belonging to 17 lineages, predominantly including BF.7.14 (22.3%), DY.2 (17.3%), DY.4 (15.5%), and BA.5.2.48 (11.9%). The Rt value increased rapidly after mid-November 2022, reaching its peak at the end of the month. We identified forty-three core mutations in the S gene and forty-seven core mutations in the ORF1ab gene. The positive selection of all circulating lineages was primarily due to non-synonymous substitutions in the S1 region. These findings provide insights into the genomic characteristics of SARS-CoV-2 genomes in China following the relaxation of the 'dynamic zero-COVID' policy and emphasize the importance of ongoing genomic monitoring.